(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article deals with the monitoring and security of modern networks. The article analysed the design of re-installation of existing Wi-Fi networks or the design of planned new Wi-Fi networks, ensuring their quality service, cyber security issues. In particular, the steps taken to protect corporate networks from outside interference, their damage, and ensure their high level of security were discussed, reliable networks, their support, and ensuring the protection of network infrastructure were discussed. Systems and software created for the detection and cleaning of virus programs and intrusions were examined. In addition, the people interfering with the network and their interventions are indicated. For this purpose, protection methods and a new monitoring system for the creation of security operation centres in companies to protect against attacks and to increase trust in networks were mentioned.